Perubahan Kepemimpinan Karismatik Menuju Distorsi Otoritas: Jejak Malapraktik Kekuasaan Kiai dalam Sejarah Pesantren - Alwi, Khanabi; Abdurrahman, Ulinnuha; Pambudi, Ahmad Sun'an; Akmal, Ahmad Wildan Rofrofil (Qurthuba: The Journal of History and Islamic Civilization, 2026)
In the history of Islam in the Indonesian archipelago, pesantren have positioned the kiai as a central figure endowed with strong scholarly authority and charismatic leadership. However, in practice, charisma that is not accompanied by mechanisms of control and accountability may become distorted into an abuse of power. This article aims to analyze the shift of charismatic leadership toward authoritarian malpractice in the historical context of pesantren, focusing on cases of sexual violence against students as documented in a court ruling. This study employs a qualitative approach based on library research, with the primary source being Decision Number 136/Pid.Sus/PN Smp/2025 of the Sumenep District Court. The data are analyzed using a descriptive-analytical method to identify patterns of power relations, forms of religious legitimization, and their impacts on victims. The findings indicate that charismatic leadership, when detached from ethical control and structural oversight, has the potential to transform into an instrument of domination that facilitates sexual violence rooted in hierarchical relations and absolute obedience. The case examined reveals a significant gap between the ideal image of the kiai as a moral guardian of the pesantren and the empirical reality of distorted authority that undermines students’ dignity. This study underscores the importance of historical reflection and structural evaluation of pesantren leadership models to preserve the integrity of pesantren as educational and moral institutions within Islamic civilization.